2016
DOI: 10.18632/oncotarget.7466
|View full text |Cite
|
Sign up to set email alerts
|

Activated-PAK4 predicts worse prognosis in breast cancer and promotes tumorigenesis through activation of PI3K/AKT signaling

Abstract: The p21-activated kinase 4 (PAK4) is sufficient to transform noncancerous mammary epithelial cells and to form tumors in the mammary glands of mice. The accumulated information suggests that PAK4 might be an oncogenic protein in breast cancer. In this study, we sought to identify the role for PAK4 in breast cancer progression. Immunohistochemical study revealed that high PAK4 expression is associated with larger tumor size, lymph node metastasis, and advanced stage cancer in 93 invasive breast carcinoma patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 37 publications
(60 reference statements)
2
41
1
Order By: Relevance
“…These findings echo the results from other studies in breast and ovarian cancer [16]. There has been limited data in PDAC, although one small retrospective study surprisingly demonstrated that lower levels of PAK4 expression was associated with worse survival and tumor characteristics [17].…”
Section: Pak4: a Potential Prognostic Biomarkersupporting
confidence: 86%
“…These findings echo the results from other studies in breast and ovarian cancer [16]. There has been limited data in PDAC, although one small retrospective study surprisingly demonstrated that lower levels of PAK4 expression was associated with worse survival and tumor characteristics [17].…”
Section: Pak4: a Potential Prognostic Biomarkersupporting
confidence: 86%
“…In most adult tissues, PAK4 expression is low. However, its overexpression has not only been associated with oncogenic transformation [29,30], but also with disease stage in breast clinical specimens [31][32][33]. We found that PAK1/4-driven CSC activity increased as the disease progressed in sequential metastatic samples taken from 2 ER+ breast cancer patients.…”
Section: Discussionmentioning
confidence: 76%
“…Data supporting a role in breast cancer include oncogenic transformation of immortalised mouse mammary epithelial cells by PAK4 overexpression and PAK4 RNAi reversing the malignant phenotype of MDAMB231 breast cancer cells [29,30]. Moreover, 3 independent studies on the expression of PAK4 in breast clinical specimens at different disease stages showed that high protein levels correlate with larger tumour size, lymph node involvement and invasive disease [31][32][33]. Furthermore, PAK4 expression associates with poor clinical outcome in tamoxifen-treated patients and was demonstrated to positively regulating ER transcriptional activity in an endocrine resistant breast cancer cell line [34].…”
Section: Introductionmentioning
confidence: 99%
“…PAK4 is involved in a variety of cytoskeletal regulation such as promoting filopodia formation, dissolution of stress fibers, controlling actin polymerization and depolymerization as well as focal adhesion turnover [19][20][21][22][23][24][25] . Consistently, PAK4 overexpression is correlated with poor patient outcome in breast cancer patients, and its overexpression in breast cancer cell lines was shown to increase cell survival, anchorage-independent growth, cell migration and invasion [26][27][28][29][30] . PAK4 also plays an essential role during embryonic development, as complete depletion of PAK4 in mice caused embryonic lethality with severe defects in the heart, brain, and vasculature of the animals; however, its role in mammary gland development has not been investigated [31][32][33] .…”
Section: Introductionmentioning
confidence: 76%